Urgensi Peran Guru PAI dan Guru BK Dalam Membentuk Akhlaqul Karimah Siswa (Studi di MAN 1 Rangkasbitung Lebak Banten) - Rikaeni Munada, Ike; Hilmiyati, Fitri; Firda Nadhirah, Yahdinil; Wasehudin; Ahmad Lugowi, Rifyal (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
This study aims to examine the urgency of the role of Islamic Religious Education teachers and BK teachers in shaping students' noble character at MAN 1 Rangkasbitung Lebak Banten. In the context of Islamic education, the formation of noble character is the main goal of educational institutions. However, the phenomena of globalization, technological developments, and free association are challenges in shaping students' character. This study uses a qualitative approach with a case study method. Data collection was carried out through observation, in-depth interviews with Islamic Religious Education teachers and BK teachers, and documentation. The results of the study indicate that Islamic Religious Education teachers play an important role in developing character-based learning and the habituation of noble character, while BK teachers play a role in character-based classical guidance services, individual and group mentoring, and home visit and parenting programs. The main challenges in shaping students' character include the negative influence of social media and the internet, limited time allocation for Islamic Religious Education learning, and lack of optimal support from the family environment. This study concludes that collaboration between Islamic Religious Education teachers and BK teachers is very important in shaping students' noble character through a comprehensive approach involving the madrasah, family, and community